Developing the therapeutic relationship : integrating case studies, research, and practice - Tishby, Orya; Wiseman, Hadas, 1956- (American Psychological Association, 2018)
"During the last 2 decades, remarkable progress has been made in psychotherapy research, specifically in the development of evidence-based treatments for a range of disorders. This book examines the development of the therapeutic relationship through different "lenses" based on theory, research, and practice. Research on the therapeutic alliance shows that its contribution to outcome cuts across theoretical orientations; however, it is argued that this process develops in different ways in various types of therapies. The authors of the chapters are clinicians who are also psychotherapy researchers; they faced the challenge of integrating their case studies with research and practice. In each chapter, they present a relationship conceptualization that guided them (involving both patient and therapist) and demonstrate through the case study how it contributes, together with technique, to successful outcome. The book begins with an overview of the therapeutic relationship, and its centrality to the therapeutic process. The chapter presents four main theoretical "threads," delineating different functions of the client-therapist relationship and how they facilitate therapy process. The chapter emphasizes the need to discover which parts of the therapy relationship are shared among different kinds of treatments, and which parts are unique. It also recommends examining specific ways in which the interactive nature of psychotherapy is differently manifested and utilized in a variety of contexts. Eleven clinical case studies follow, describing a variety of relationship aspects and how they are manifested in different therapies."--Preface. (PsycINFO Database Record (c) 2018 APA, all rights reserved)